2018
DOI: 10.3906/biy-1805-103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term administration of Cinnamomum cassia silver nanoparticles on organs (kidneys and liver) of Sprague-Dawley rats

Abstract: This study investigated the toxic effects of silver on the kidneys and livers of Sprague-Dawley rats after administering multiple doses of silver nanoparticles synthesized using extracts of Cinnamomum cassia (CcAgNPs). Twenty-four Sprague-Dawley rats (250 ± 20 g) were randomly assigned to four groups (A-D) of six animals per group and treated for 8 weeks. Group A was administered 200 mg/kg of Cinnamon Cassia extract (Cc), group B 5 mg/kg of CcAgNPs, group C 10 mg/kg of CcAgNPs, and group D normal saline. Body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…In the kidney specimen, they found mild morphological alterations in the glomeruli of the rat kidney which were given 5 mg/kg of silver nanoparticles (from cinnamomum cassia extract) while changes were more severe and generalized in the kidneys of rat exposed to 10 mg/kg of silver nanoparticles. It suggests that the increasing dose of nanoparticles produces more damaging effect [12]. In our study, the morphological changes were less severe than the study published by Kouame K et al but these are similar in this aspect that in both series, increase in the dose of nanoparticles increases the impact of damage.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the kidney specimen, they found mild morphological alterations in the glomeruli of the rat kidney which were given 5 mg/kg of silver nanoparticles (from cinnamomum cassia extract) while changes were more severe and generalized in the kidneys of rat exposed to 10 mg/kg of silver nanoparticles. It suggests that the increasing dose of nanoparticles produces more damaging effect [12]. In our study, the morphological changes were less severe than the study published by Kouame K et al but these are similar in this aspect that in both series, increase in the dose of nanoparticles increases the impact of damage.…”
Section: Discussionsupporting
confidence: 77%
“…The current study revealed that no histological evidence of the toxic effects of cinnamon nanoparticles with the dosage of 5 ppm and 10 ppm has been observed in the liver and kidney of the mice but the dosage of 20 ppm revealed certain histological alteration in the liver and kidney of the mice. A study published by Kouame K et al narrated the toxic effects of long term use of cinnamomun cassia silver nanoparticle on the kidney and liver of Sprague -Dawley rats [12]. In their study, they detected that the rat exposed to 10 mg/kg of silver nanoparticles synthesized from the cinnamomum cassia extract revealed pyknosis, vacuolar changes and distortion in the arrangement of hepatocytes of liver specimen of rats.…”
Section: Discussionmentioning
confidence: 98%
“…High correlation of these genes with inflammation, hepatotoxicity, and cancer was confirmed [ 2 ]. Histological examination of rat liver after 8 weeks of oral treatment with AgNPs in the dose of 10 mg/kg showed distortion in hepatocellular arrangement, nuclear condensation and pyknosis, and areas of vascular changes suggesting loss of liver architectural support or fibrosis [ 49 ]. These data revealed that silver exposure in the form of nanoparticles could provoke multifaceted, continued, and prolonged damage of liver tissue structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a 13-week repeat-dose oral toxicity study revealed that body weights of rats were normal, the weight of kidney/live and the level of total cholesterol were increased after receiving WEBC at up to 2000 mg/kg, but it was not mutagenic or clastogenic [111]. Later, a 8-week repeat-dose oral toxicity study revealed that renal function showed a significant increase, kidney and liver histology showed distortions in hepatocytes and sinusoidal linings with infiltrations, degenerative changes in glomerular and Bowman’s capsules with fibrillary mesangial interstitium after receiving CcAgNPs at up to 200 mg/kg [112]. In summary, C. cassia essential oil may cause skin irritation and its extract may possess potential nephrotoxicity and hepatotoxicity at dose higher than its recommended daily safe dose.…”
Section: Toxicitymentioning
confidence: 99%